HUBUNGAN DUKUNGAN SOSIAL TEMAN SEBAYA, KONTROL DIRI, DAN JENIS KELAMIN DENGAN PRESTASI BELAJAR SISWA DI SMA KRISTEN YPKPM AMBON - Salomina Patty; Sutarto Wijono; Adi Setiawan (PSIKODIMENSIA, 2016)
control and gender with student’s learning achievement in SMA Kristen YPKPM Ambon. The population in this research is the whole students of SMA Kristen YPKPM Ambon which amounts 797 students, while the number of the samples that has been used in this research were 168 students. To measure the variable of social support of peers it has been used questionnaire adapted by Malecki (2002, cited in Dewolff 2012). To measure the variable of self-control it has been used questionnaire by Tangney et al (2004) which is then used by Gong, et al (2009) on his research, while the student’s achievement has been measured using the report of students education in the first semester period 2013/2014. Before testing thehypothesis, first is measuring the validity and reliability of measuring instruments by using a standard p>0.30 for validity and p>0.70 for reliability. After the writer/researcher test the hypothesis, then there are some research results as follows: there is was relationship of peer social support and self-control with student achievement, there is no interaction effect of peer social support and gender with student achievement, there is no interaction effect of self control and gender with student achievement, there is no interaction effect of peer social support, self control and gender with student achievement, and there was difference in student learning achievement in terms of gender